If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-17+47=-5(x+4)
We move all terms to the left:
-17+47-(-5(x+4))=0
We add all the numbers together, and all the variables
-(-5(x+4))+30=0
We calculate terms in parentheses: -(-5(x+4)), so:We get rid of parentheses
-5(x+4)
We multiply parentheses
-5x-20
Back to the equation:
-(-5x-20)
5x+20+30=0
We add all the numbers together, and all the variables
5x+50=0
We move all terms containing x to the left, all other terms to the right
5x=-50
x=-50/5
x=-10
| 5.3x=-21.2 | | 20+x/4=22 | | -15=6-1/2x | | 66+12x=234 | | t-15=24 | | 5(2x-10)=100 | | -24-8x=-2(-3x+7) | | -147x=27 | | 2(5x+9)=-45+33 | | 11x+127=-38 | | 10x(34+4)=4x | | 69x(420)÷3=4x | | 4x=-11-6x-9 | | 30+2x-7=20 | | 2(4x+6)=-22+26 | | -5/3=8/5v | | 3y-150=1778 | | x=x+4=3x-9 | | 2x-4=3x+5=2x+11 | | 1-3=4x/3 | | 55=8+7(k-5) | | 16v-12v+12v-7v+1=10 | | -5x-18=-68 | | 37s-13s+2s-4s-4=40 | | (1)/(x+1)^2-(2)/(x+1)+2=0 | | -3/4(12w-24)=4w-(13+12) | | 33d-19d-6d+6d-9d+3=18 | | n/5-6=-2 | | -3x+22=16 | | 8((-1+m)+3=2(m-51/2) | | 10x-4x=11x+5 | | (2x+2)^2=0 |